2015
DOI: 10.1177/0021886315576190
|View full text |Cite
|
Sign up to set email alerts
|

Ethical Codes and Executive Coaches

Abstract: While most coaching scholars and professionals focus on the role of codes of conduct in sustaining ethical behavior in the practice of executive coaching, our research answers the call to go "beyond the book." Our study aims to describe restrictions identified by executive coaches to the application of codes to ethical conflicts. The analysis of 27 coaches' ethical challenges highlights three main types of restrictions that coaches express: the code is not relevant, the code has shortcomings, and the code is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Fischer et al (2017) propose the use of an event-based "person-parts" approach, whereby events are seen as "episodes where actions intersect with a context" (p. 1736). This approach is promising and reflects recent EC outcome studies on the critical incidents of EC interventions allowing to capture the social context and actors' interaction at several points in time (De Haan, Bertie, Day & Sills, 2010;De Haan & Nies, 2012;Turner & McCarthy, 2015;Diochon & Nizet, 2015).…”
Section: Key Challenges For Ec Researchmentioning
confidence: 95%
“…Fischer et al (2017) propose the use of an event-based "person-parts" approach, whereby events are seen as "episodes where actions intersect with a context" (p. 1736). This approach is promising and reflects recent EC outcome studies on the critical incidents of EC interventions allowing to capture the social context and actors' interaction at several points in time (De Haan, Bertie, Day & Sills, 2010;De Haan & Nies, 2012;Turner & McCarthy, 2015;Diochon & Nizet, 2015).…”
Section: Key Challenges For Ec Researchmentioning
confidence: 95%
“…Given the diversity of the topics covered under the project, it was not feasible to produce a single integrative article that presents all the results from the entire data set in a meaningful way. Each article developed from this data set (Fatien Diochon & Nizet, 2015, 2019Pichault, Fatien Diochon, & Nizet, 2020) addresses a different research question, uses different relevant literature, and has a distinct purpose.…”
Section: Research Context: Executive Coachingmentioning
confidence: 99%
“…While the ability to navigate within these multiple camps is perceived as the key for an activity on its way towards professionalization and legitimization (Gray et al, 2016), it is far from straightforward. There are times when holding multiple roles or facing contradictory requests becomes extremely difficult, to the point that it may raise ethical dilemmas (Fatien Diochon & Nizet, 2015, 2019Louis & Fatien Diochon, 2019). Exploring how coaches make ethical decisions when they experience conflicting commitments is the focus of this study.…”
Section: Research Context: Executive Coachingmentioning
confidence: 99%
“…A research study analyzed 27 coaches' ethical challenges, and found three main types of restriction in ethical codes: 1) the code is not relevant; 2) the code has shortcomings; and 3) the code is an obstacle to the ethics of the coach, leading the researchers to conclude that "legitimacy, efficacy, and value issues show that codes do not fit all situations or all practitioners" (Diochon and Nizet, 2015).…”
Section: Philosophy Of Coaching: An International Journal 11mentioning
confidence: 99%